Worshippers of the Gods: Debating Paganism in the Fourth-Century Roman West - Gassman, Mattias (Oxford Studies in Late Antiquity Ser., 2020)
Worshippers of the Gods shows how fourth-century Latin writers rethought traditional religion during Christianity's rise. Through five interlocking studies of inscriptions, laws, senatorial papers, and Christian polemics, it traces shifting conceptions of paganism from the Tetrarchic persecution, through Constantine's reign, to the 'disestablishment' of the Roman cults in the 380s.